Taxonomic Study of Six Sargassum Species (Sargassaceae, Fucales) with Compressed Primary Branches in the Persian Gulf and Oman Sea Including S. binderi Sonder a New Record Species for Algal Flora, Iran - M. Shams; S. Afsharzadeh; Gh. Balali (Journal of Sciences, Islamic Republic of Iran)
Six species of Sargassum C. Agardh (Sargassaceae) with compressed primary branches, including: S. binderi Sonder, S. aquifolium (Turner)C. Agardh, S. oligocystum Montagne, S. swartzii (Turner)C. Agardh, S. crassifolium J. Agardh and S. cristaefolium C. A. Agardh, were identified in the Persian Gulf and Oman Sea coasts, among which S. binderi is reported as newly recorded species in Iran for the first time. The specimens were collected from 15 stations along the Iranian southern shores in the autumn, winter and spring from 2010 to 2012. Anatomical and morphological studies were performed according to the valid identification keys. In taxonomy studies, 47 quantitative and qualitative morphological characters were selected. In order to analyze of data, clustering analysis was performed by UPGMA and PCA analyses. The results revealed that there were more qualitative than quantitative traits in species identification.  The shape of receptacles, leaves, vesicles and stems were the most diagnostic characteristics in the species identification. The species including: S. binderi, S. crassifolium and S. cristaefolium have flattened triangular receptacles; while S. crassifolium and S. cristaefolium have duplicated leaves with fine teeth; S. swartzii has linear lanceolate leaves, pointed or crowned vesicles and S. oligocystum has broader lanceolate leaves with an acute to rounded apex, and often entire and spherical vesicles. S. oligocystum and S. crassifolium belong to the section Acanthocarpicae. Also, S. cristaefolium belongs to section Sargassum and S. binderi, S. aquifolium and S. swartzii belong to section Binderianeae.